2021
DOI: 10.1097/jom.0000000000002446
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Lipid Metabolism Despite Fitness Improvements in Wildland Firefighters

Abstract: Despite high levels of physical activity amongst wildland firefighters on standard assignments, maladaptive changes in serum lipids and adipose tissue present in this cohort over a season of wildfire suppression. Therefore, the commonly known benefits of exercise may be negatively affected by the multifactorial stressors of this occupation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(186 reference statements)
0
4
0
Order By: Relevance
“…Despite these acute improvements in cardiovascular and metabolic health, previous research has established detrimental alterations across a single fire season. 15,16 In 2019, Coker et al 15 showed seasonal increases in total cholesterol and LDL-C in a single crew. These results were confirmed across multiple crews in 2022, showing negative modifications in total cholesterol, LDL-C, VLDL-C, HDL-C, and total triglycerides.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite these acute improvements in cardiovascular and metabolic health, previous research has established detrimental alterations across a single fire season. 15,16 In 2019, Coker et al 15 showed seasonal increases in total cholesterol and LDL-C in a single crew. These results were confirmed across multiple crews in 2022, showing negative modifications in total cholesterol, LDL-C, VLDL-C, HDL-C, and total triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…These results were confirmed across multiple crews in 2022, showing negative modifications in total cholesterol, LDL-C, VLDL-C, HDL-C, and total triglycerides. 16 Importantly, the postseason values across these crews were quantitatively similar to those seen in the current study before CT. This suggests that despite the acute improvements seen in CT, it does not provide long-term cardiovascular and metabolic protection for WLFFs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations